(untitled) (Journal of Buffalo Science, 2023)
Background: The current study aims to measure the effect of oxidative stress on the pregnancy rates of Bulgarian Murrah buffaloes during the breeding and non-breeding season. Methods: The study group consisted of 24 mature buffaloes more than 40 days after parturition. The following parameters were measured: Reactive Oxygen Species (ROS) products, Ascorbate radicals, Malondialdehyde (MDA), Nitric Oxide (NO), Super Oxide Dismutase (SOD), Glutathione peroxidase (GSH-Px), Protein Carbonyl Content (PPC), and total Nitric oxide. The Presynch/Ovsynch protocol was used for estrus synchronization. Results: A statistically significant increase in ROS products were measured in blood serum during the breeding season compared with the non-breeding season. The highest levels measured were in non-pregnant buffaloes during the breeding season. High levels of oxidative stress were registered due to low SOD activity in buffaloes during the breeding season compared to SOD activity during the non-breeding season. The highest SOD activity was observed in non-pregnant buffaloes during the summer season. The lowest GSH-Px levels were observed in non-pregnant buffaloes during both study periods. During the breeding season, concentrations of total NO and PPC were elevated. Conclusion: Comparing the obtained results for oxidative stress and antioxidant activity concerning pregnancy rate depending on the season showed that pregnancy in buffaloes during the breeding season was realized at higher values of NO and SOD. Increased oxidative stress was observed, resulting in a statistically significant increase in serum ROS products, as well as decreased SOD activity in buffaloes during the breeding season.